Lameness in dairy cattle - Gerald L. Stokka; John F. Smith; James R. Dunham; Anne T. Van (Kansas Agricultural Experiment Station Research Reports, 1996)
Foot problems are major concerns for dairies, and care should be taken to avoid promoting them. Preventive measures, with the aid of a veterinarian, must be followed if the problem is expected to be controlled. Feet should be trimmed or at least observed one to two times per year. High concentrate diets should be fed carefully to avoid acidosis. Cows should have limited time standing on concrete and should not be rushed when walking on any abrasive surfaces. Cows need a clean, comfortable environment in which to lie down. Lame cows need treatment early, and records should be kept on all cases.; Dairy Day, 1996, Kansas State University, Manhattan, KS, 1996;
Keywords: Dairy Day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-115-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 771; Hoof health; Lameness; Foot rot